Nutmeg Extract Alters Mitochondrial Genes Regulation of Skeletal Muscle Fibers in Aging Rats - Setiawan, Setiawan; Pratiwi, Yuni Susanti; Lesmana, Ronny; Sari, Galuga Sinalusur; Ramdan, Ahmad; Hartono, Aldo; Fathurachman, Fathurachman; Supratman, Unang (Majalah Kedokteran Bandung, 2022)
Nutmeg as one of Indonesia native plants has already been used widely in herbal treatment. It has been demonstrated that nutmeg presents activities related to mitochondria functions. Nutmeg potentially has the effect of peroxisome proliferator activated receptors Î¥ (PPAR Î¥) which contributes to myogenesis, and may alters mitochondrial homeostasis in respiration and biogenesis. In this study, how nutmeg extract alters oxidative process in skeletal muscle of aging rats was explored. Twenty aging Wistar male rats aged 80 weeks old were divided into two groups (control and nutmeg treatment). Nutmeg extract was administered for 12 weeks using a gavage. After that, the soleus muscles were collected, weighted, frozen, and stored at -800C until used. Nutmeg was observed to increase the COX1 (1.9 folds, p<0.01), COX2 (1.6 folds, p<0.05), and COXIV (2.8 folds, p<0.01) gene expressions, in parallel with increased protein carbonyl levels (1.5 folds, p<0,01). Nutmeg treatment also significantly increased the expressions of antioxidant endogen COQ7 (2 folds, p<0,01) and PDSS2 (2 folds, p<0,01) in the soleus muscle. Taken together, nutmeg extract may improve mitochondrial respiratory oxidative activities in type I aging skeletal muscle.